THE EFFECTIVENESS OF WEB-BASED MULTIMEDIA APPLICATIONS SIMULATION IN TEACHING AND LEARNING IN AHMEDABAD RURAL AREA. - Manubhai, Solanki Ankit; Patoliya, Virali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study focuses on the effectiveness of using web-based multimedia applications simulation in teaching and learning in Ahmedabad rural area. Virtual simulation methods embedded in online platforms were used in this study to determine the effectiveness of these modes in motivating students on complex subjects. The topic of science experiments was chosen because conducting physical experiments is often challenging due to the lack of laboratory facilities in rural schools. Web-based multimedia simulations allow students to interact with a virtual environment that closely resembles real-life scientific experiments. This study was conducted using a 2x2 factorial experimental design, and a quasi t-test was used as a method of analysing the data. The findings of this study show that the use of web-based multimedia simulation helps students to enhance their understanding and achievement in science subjects. The study highlights that web-based simulations offer an innovative approach to overcome geographical and infrastructural barriers in education. By integrating interactive and visually rich simulations, students in Ahmedabad rural area can engage with the subject matter in an immersive and effective manner, ultimately improving their learning outcomes.